Marginal bone resorption at dental implant - RTG analysis - Pejeva E; Papakoca K; Ambarkova V; Todorovska G (Journal of Dental Problems and Solutions - Peertechz Publications, 2018)
Dental implants are modern solutions, they compensate the lost tooth or teeth in the maxilla or mandible. Their target is to improve the mastication, esthetics and phonation. They are made of metal,metal alloys or non-metallic materials. An important factor for successful implantation is biocompactibility. Bone resorption is destruction of bone tissue, and the loss of bone tissue is conducted by osteoclasts and mononuclear cells. In this fi nal paper are described the peri-implant diseases exactly the peri-implant mucositis and peri-implantitis. This diseases are complication of ossteointegrated dental implants, and they make changes of the soft and bone tissue around the implant. They bring marginal bone resorption, around the dental implant, and they do destruction of the bone tissue. RTG analysis were made, with intention to see how much the marginal bone resorption is around the dental implants.